Total phenolic contents, cytotoxic, free radicals, porcine pancreatic α-amylase, and lipase suppressant activities of Artemisia dracunculus plant from Palestine - Jaradat, Nidal; Dwikat, Majdi; Amer, Johnny; Ghanim, Mustafa; Hawash, Mohammed; Hussein, Fatima; Issa, Linda; Ishtawe, Salsabeel; Salah, Shahd; Nasser, Sara (Frontiers in Pharmacology, 2024)
Artemisia dracunculus: L. (A. dracunculus) is a popular vegetable and spice cultivated across many Middle Eastern countries. The herb’s aqueous extract has significant folkloric medicinal importance for treating various disorders. Hence, the present investigation aimed to investigate A. dracunculus hydrophilic extract phytochemical constituents and pleiotropic biological potentials, as no previous studies have investigated the antilipase and anti-α-amylase effects of the A. dracunculus plant. Total phenol content and phytochemical screening assays were performed utilizing standard analytical methods. While the α-amylase inhibition, free radical-scavenging, antilipase, and cytotoxic activities were determined using dinitrosalicylic acid (DNSA), DPPH, p-nitrophenyl butyrate (PNPB), and MTS assays, respectively. The standard phytochemical analysis of A. dracunculus aqueous extract shows that this extract contains only a phenolic group. The total phenol content was 0.146 ± 0.012 mg GAE/g of the plant dry extract. The A. dracunculus aqueous extract exhibited potent DPPH free radical inhibitory (IC50 dose of 10.71 ± 0.01 μg/mL) and anti-lipase activities (IC50 dose of 60.25 ± 0.33 μg/mL) compared with Trolox (IC50 = 5.7 ± 0.92 μg/mL) and Orlistat (IC50 = 12.3 ± 0.35 μg/mL), respectively. However, it showed a weak anti-α-amylase effect (IC50 value > 1,000 μg/mL) compared with Acarbose (IC50 = 28.18 ± 1.27 μg/mL). A. dracunculus has a cytotoxic effect against the HeLa cancer cell line compared with the chemotherapeutic agent Doxorubicin. The extract has the same percent of inhibition as Doxorubicin (99.9%) at 10 mg/mL. Overall, these results pointed out for the first time the importance of considering A. dracunculus effects as a favorite candidate for preventing and treating metabolic disorders. Also, our results confirm the findings of previous reports on the role of A. dracunculus in the management of cancer and disorders resulting from the accumulation of harmful free radicals. On the contrary, the current study concluded that the antidiabetic role of A. dracunculus could be minimal. Further in-depth investigations are urgently warranted to explore the importance of A. dracunculus in pharmaceutical production.